2016
DOI: 10.5539/jel.v5n4p126
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Silence in Sports Employees

Abstract: Organizational silence can be defined as a way of behaviour belonging to men and women employees in the organization exhibited without reflecting their feelings, ideas, concerns and suggestions related with their workplaces, works for which they are responsible or other activities of the organization. In the period of organizational silence, silence, in other words, decision of not talking clearly about problems and subjects, is an important subject to be laid emphasis on when it is considered that it prevents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Although exposure to mobbing is reported in these studies, no significant difference could be found between the genders. On organizational silence, Bastug et al (2016), Demirtaş & Nacar (2018), Near &Miceli (1996) have similar research findings. In these studies, it has been reported that women exhibit higher levels of organizational silence in their workplaces.…”
Section: Discussionmentioning
confidence: 58%
“…Although exposure to mobbing is reported in these studies, no significant difference could be found between the genders. On organizational silence, Bastug et al (2016), Demirtaş & Nacar (2018), Near &Miceli (1996) have similar research findings. In these studies, it has been reported that women exhibit higher levels of organizational silence in their workplaces.…”
Section: Discussionmentioning
confidence: 58%
“…Hirschman (1970) developed the basis for work on employee silence and considered it as behavior to remain silent with wish that things would be better in future. Employee silence is a behavior in which employees lack their own actions, apprehensions and recommendations relating to their assigned work (Bastug et al, 2016). Employee silence is a behavior in which employee opts to remain quiet and stops giving opinion in an organization in order to remain safe from consequential outcomes (Nafei, 2016)…”
Section: Absorptionmentioning
confidence: 99%